The Impact Of Percieved Ease of Use, Brand Awareness And Freemium Business Model on Buying Interest of Spotify Users In Medan City - Mirza Abdillah Pane; Endang Sulistya Rini; Beby Karina Fawzeea (CERED Indonesia Institute, 2022)
The rapid development of internet technology causing significant impact of innovative disruption in any aspect of life, especially on music industry. Disruptive innovation is a very new innovation made for competing the challengers in the music industry. The people consumption of music has been shifted because of the technology. From CD’s or cassettes into digital album. These digital albums are provided by the music streaming apps. The music streaming apps need to offer the most attractive innovation to attract user’s attention in aim the user’s buying the premium package. Known that the perceived ease of use, brand awareness, and free trial can be useful in attract buying interest of the users. The music streaming apps in this theses is Spotify. The goal of this theses is to analyze the impact of percieved ease of use, brand awareness and freemium business model on buying interest of spotify users in medan city. This theses is a associative causal, quantitative approach. The population of this theses are the users of spotify apps in medan city, and the samples are 100 respondents. The sampling methods is incidental sampling. Data analysis is multiple regression analysis to be analyzed in SPSS. The results is percieved ease of use has positive and significant impact on buying interest, brand awareness has positive and significant impact on buying interest, and freemium business model has positive and significant on buying interest. The percieved ease of use, brand awareness, and freemium business have simultaneously impact on buying interest.